2017
DOI: 10.1088/1361-6455/aa8572
|View full text |Cite
|
Sign up to set email alerts
|

Electron scattering from molecules and molecular aggregates of biological relevance

Abstract: In this Topical Review we survey the current state of the art in the study of low energy electron collisions with biologically relevant molecules and molecular clusters. We briefly describe the methods and techniques used in the investigation of these processes and summarise the results obtained so far for DNA constituents and their model compounds, amino acids, peptide and other biomolecules. The applications of the data obtained is briefly described as well as future required developments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 272 publications
(434 reference statements)
0
68
0
2
Order By: Relevance
“…cisplatin) have also been studied. 3 However, the scattering community has paid significantly less attention to other types of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…cisplatin) have also been studied. 3 However, the scattering community has paid significantly less attention to other types of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effort was placed into the study of electron scattering form DNA components, particularly nucleobases both experimentally (the focus being on studying DEA by mass spectroscopy) and, later on, computationally (where a lot of emphasis has been placed on the investigation of the temporary negative ions, or resonances, that lead to DEA). The work has more recently been extended to other types of biomolecules, in particular aminoacids 3 .…”
Section: Introductionmentioning
confidence: 99%
“…LEE-induced damage to DNA was first experimentally demonstrated by Sanche and his co-workers who showed that LEE irradiation resulted in single-and double-strand breaks in DNA [3]. Since then, many experimental and theoretical works [1,[4][5][6][7][8] have been devoted to the LEE-induced fragmentation of biomolecules to obtain a comprehensive picture of the damage mechanism. It has been shown that shape (Fig.…”
mentioning
confidence: 99%